NILAI- NILAI PENDIDIKAN DALAM KEKAWIN SUTASOMA - Sumariani, Ni Putu (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
Bali is famous for the work of local wisdom in the form of a literary heritage written or unwritten. Is written in the form of literature and Hindu literature. In addition to the Mahabrata and Ramayana literature literary one that is believed by Hindus that contain the teachings and value of education is Kakawin Sutasoma. From the teachings and values contained in an initial from of protection in the younger generation to fortify exhume literary sources capable of providing education Hinduism. Relating to these dimensions, Kakawin Sutasoma is kakawin that tells very deep teachings which in this kakawin reveals Shiva and Buddha's teachings which basically both these teachings single existence. Therefore Kakawin Sutasoma is often Sung every Hindu religious ceremony in Bali.